Curcumin enhances GSDME-mediated pyroptosis to potentiate PD-1/PD-L1 immune checkpoint blockade in colorectal cancer - Tan, Dongsheng; Li, Gengdong; Li, Xiaoda; Zhai, Weiwei; Jing, Lijia (Frontiers in Pharmacology, 2026)
Colorectal cancer (CRC) patients with a microsatellite-stable (MSS) status exhibit poor responsiveness to PD-1/PD-L1 blockade. Pyroptosis induction may resensitize MSS tumors to PD-1/PD-L1 blockade; however, the expression of GSDME, a key executor of pyroptosis, is often downregulated in CRC. Here, curcumin (CUR), a natural polyphenol, was identified as a potentiator of GSDME-dependent pyroptosis in CRC. We discovered that CUR upregulates GSDME expression by inhibiting the ubiquitin–proteasome system (UPS) in the MSS-type CT26 and HT29 cell lines and activating the caspase-3/GSDME signalling axis, resulting in increased pyroptosis. In CT26 tumors, CUR-enhanced pyroptosis reshaped tumor-infiltrating immune subsets and potentiated the efficacy of anti–PD-1 therapy. Notably, the synergistic antitumor activity of CUR combined with PD-1 blockade in CT26 tumors is strictly dependent on the caspase-3/GSDME axis, as the therapeutic benefit was abolished in GSDME-knockout tumors. These findings establish CUR as a safe and effective adjuvant for PD-1/PD-L1 blockade in MSS CRC, particularly in tumors with low GSDME expression.